The pathological mechanism of the COVID-19 convalescence and its treatment with traditional Chinese medicine - Jiang, Linlin; An, Xuedong; Duan, Yingying; Lian, Fengmei; Jin, De; Zhang, Yuehong; Yang, Cunqing; Zhang, Yuqing; Kang, Xiaomin; Sun, Yuting (Frontiers in Pharmacology, 2023)
Format：By the severe acute respiratory syndrome coronavirus - 2 (SARS - CoV - 2) caused by 2019 corona virus disease (COVID - 19) broke out in 2019 for the first time in wuhan, China.As of 19 December 2021, the SARS - CoV - 2 has left 274.38 million people infected, at the same time, the SARS - CoV - 2 have strong ability of variation, the latest mutant Omicron was discovered in the globe, growing Numbers of infections caused by.After systemic treatment, the virus in most patients with SARS - CoV - 2 is considered to have been cleared and can be discharged normally. With the successive discharge of many patients with infection, the number of patients in the recovery period has gradually increased. They suffer from multiple system and multiple symptoms such as fatigue, dyspnea and pain in the recovery period. These symptoms are called "long-COVID", "post-COVID syndrome" or recovery sequelae. Methods：We mainly searched PubMed for articles involving covid-19 recovery period. In addition, CNKI and Wanfang were also used as supplements. English retrieval formula: ((((Rehabilitation"[Mesh]) OR (Convalescence" [Mesh])) OR (recovery phase [Title/Abstract])) OR (recovery period [Title/Abstract])) AND (COVID-19" [Mesh]). Result：We found that the pathogenesis of covid-19 convalescence is not yet well recognized, therefore，we summarized the possible pathogenesis of the recovery period of the covid-19.We also found that the effect of traditional Chinese medicine in the treatment of the recovery period of the covid-19 is significant, which can not only relieve the corresponding symptoms, but also improve the indicators and pulmonary fibrosis. In addition, in previous studies, traditional Chinese medicine has been confirmed to have the ability to resist cytokine storm and improve coagulation and myocardial damage, which makes it have potential therapeutic advantages in targeting the hyperimmune response, coagulation abnormalities and myocardial damage existing in the recovery period.